LIPID TRENDS ON DONOR DERIVED ATHEROSCLEROTIC DISEASE AND ALLOGRAFT VASCULOPATHY IN HEART TRANSPLANT RECIPIENTS AT A LARGE ACADEMIC CENTER - Antoinette S. Birs, MD; Eric D. Adler, MD; Pam R. Taub, MD; Michael Wilkinson, MD (Elsevier, 2023)
Therapeutic Area: ASCVD/CVD in Special Populations Background: Prior studies demonstrate an association between statins and reduction in mortality and incidence of coronary allograft vasculopathy (CAV) following heart transplant, and while lipid lowering with LDL < 100 mg/dL is associated with reduced risk of CAV and delayed time to first CAV diagnosis, little is known about real-world trends in atherogenic lipids following heart transplant. We aim to describe lipid trends and CAV in a contemporary cohort of heart transplant recipients. Methods: Single-center, retrospective study of consecutive heart transplant recipients having received transplant between 01/01/2019 and 12/31/2020. Intravascular ultrasound (IVUS) during coronary angiography was performed and lipid panels were performed annually, starting at one-year post-transplant. Baseline lipids were the closest available results performed prior to transplant. Per site protocol, all patients were initiated on Pravastatin 20mg and Aspirin 81mg prior to discharge unless contraindicated. Two-sample t tests, Wilcoxon, and Kruskal-Wallis tests were performed for statistical analysis. Results: 142 Heart transplants were performed within the designated study period; 87 patients were included in the study. Most patients were male (75.3%), Caucasian (40%), median age 59 years, and median BMI 25.4 kg/m2, 78.8%, had a history of non-ischemic cardiomyopathy. Median atherogenic lipid values two years following transplant were higher when compared to pre-transplant (LDL-C: 69.5 vs 86.5 mg/dL, p=0.03, non-HDL-C:91.5 vs 118, p < 0.001, triglycerides: 94.5 vs 133, p=0.04, and remnant cholesterol 18 vs 27, p< .05). With respect to CAV outcomes two years post-transplant, LDL-C was significantly higher in patients with severe class 4 CAV. Conclusions: There is a significant increase in atherogenic lipids 2 years after heart transplant, and higher levels of LDL-C are seen in those with severe CAV. Thus, there is a clinical need to further lower atherogenic lipids in patients after heart transplant. Limitations: Analysis of confounding variables to confirm these findings and investigate the differences CV outcomes between patients with elevated lipids.